Corrigendum to "Effects of laser acupuncture in a patient with a 12-year history of facial paralysis: A case report" [Complement. Ther. Med. 43 (April) (2019) 306–310]. (June 2019) - Ton, Gil; Lee, Li-Wen; Tu, Cheng-Hao; Chen, Yi-Hung; Lee, Yu-Chen
Abstract: Background: Traumatic facial palsy, whether accidental or iatrogenic, is a common cause of facial paralysis. Laser acupuncture therapy (LAT) is a non-invasive, pain-free method to stimulate traditional acupuncture points with non-thermal laser irradiation. Low-level laser therapy has proven beneficial in the regeneration of peripheral nerves. This case report describes the feasibility of this innovative treatment in a patient with a 12-year history of traumatic facial palsy and severe sequelae. Case summary: A52-year-old male presented with a severe left-sided facial paralysis that had lasted for 12 years. At initial presentation, the man could not fully close his left eye and had difficulty eating solid foods. The paralysis of his left-sided facial muscles had resulted in dysarthria. He was administered 30 LAT sessions in the Acupuncture Department of China Medical University Hospital, Taichung, Taiwan, over a 4-month period. His recovery was monitored by scores on the Facial Disability Index, the Sunnybrook Facial Nerve Grading System and measurements of the vertical palpebral distance in his left eye. Photographs were taken after every treatment. On the 10 th treatment, a change in closure of the left eye was noticed and facial muscle strength was improved. After 22 treatments, the patient could fully close his left eye. Conclusion: LAT significantly improved the sequelae of long-term facial paralysis in this patient. Large-scale prospective studies are needed to confirm this observation.